REPRESENTATION OF MALE HEGEMONY IN CHELUCHI ONYEMELUKWE-ONUBIA’S THE SON OF THE HOUSE (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
A literary text is capable of generating multiple meaning. While the reviews of Cheluchi Onyemelukwe-Onubia’s The Son of the House had revealed the interpretation of the text through the lens of the Nigerian Civil War, violence and love; the present study subjected The Son of the House through the issue of Male Hegemony with the objectives of exploring how male hegemony was depicted in the text and how women enabled male hegemony. It adopted Sandra Bem’s Gender Schema theory as its theoretical framework, and the methodology, which is qualitative, involved the exploration of the characters in The Son of the House and how they foregrounded themselves in male hegemony. The analysis followed the tenets of Gender Schema theory; the influence of culture in perpetuating the dominance of one gender over the other and the internalization of constructed gender roles which placed one gender at a superior position than the other. The findings of this research were that patriarchal systems created room for male hegemony to thrive, which placed women in a disadvantaged situation while being subservient to the dictates of the patriarchal environment they are inhabitants of. Also, as women continued to internalize this dominance of men over them, they viewed other women who do not conform to such treatment of their persons as deviants while enabling and elevating the subjugation of women as their default setting.  This study concluded that there is an imbalance of power with the construction of gender roles, aided by customs and traditions. The people in power made rules and policies that were to the advantage of the male gender, and they were not ready to discuss the possibility of creating a level playground for both genders.
Keywords: MaleHegemony,Patriarchy,Construction,GenderRoles,Culture,Customs